What Makes Us Moral? On the capacities and conditions for being moral - Musschenga, Bert.; van Harskamp, Anton. (Library of Ethics and Applied Philosophy, 2013)
This book addresses the questionof what it means to be moral and which capacities one needs to be moral. It questions whether empathy is a cognitive or an affective capacity, or perhaps both. As most moral beings behave immorally from time to time, the authors askwhich factors cause or motivatepeople to translate their moral beliefs into action? Specially addressedis the question ofwhat is the role of internal factors such as willpower, commitment, character,and what is the role of external, situational and structural factors? Thequestions are considered from various (disciplinary) perspectives.